Community Empowerment in Well-Based Potential Welfare Improvement in Dompyong Village District Damages of Trenggalek District - Didiek Tranggono; Tukiman; Ririn P. Tutiasri; Catur Suratnoaji; Sumardjijati; Irwan Dwi Arianto (Nusantara Science and Technology Proceedings)
Trenggalek Regency has a lot of natural potential, which if got intensive touch from certain parties: Government of regency/department, related institutions, Universities through research and community service, it is possible to be able to change progress in the area of the district of Trenggalek. Example of various potentials in the village Dompyong Bendungan district, which most of the community is dairy farmers, in addition to farming cassava, corn, and vegetable crops. If these potentials get more serious attention then it is possible to change the lifestyle of a more virtuous community in improving the welfare of the community in Dompyong village. But because of the limited quality of human resources, it raises many obstacles in optimizing all the potential that exists in this village. These constraints include social, economic, cultural, and inadequate road infrastructure. Dompyong Village, Bendungan Subdistrict, Trenggalek Regency is one of the national priority villages that need to get more attention from various parties, in an effort to improve people's welfare. The objective of the activities of KKN Bela Negara Desa Prioritas Nasional is to see the potential of the village, the problems faced by the community, how to overcome the problems, and to plan the development actions in order to what efforts should be done based on the potential in Dompyong village and the target to community empowerment through dairy milk based business, post-harvest process and product, waterfall tourism development, and development of Van Dillem coffee based business. The activities of KKN Bela Negara Desa Prioritas Nasional in Dompyong Village, Bendungan District were conducted on 17-31 July 2017; and in the first year identified the following problems: (1) The intention and spirit of society that is still unstable in developing dairy cows based business and in developing SME’s (Small Medium Enterprise) based on cassava, (2) Network marketing is still weak so that hamper productivity, (3) The absence of supporting facilities in every tourist location, (4) The absence of village tourist information center, (5) Not yet integrated the various tourist sites, (6) Low public awareness in supporting the tourist village, (7) The absence of aggressive promotion of SME’s Van Dillem coffee, and (8) Infrastructure roads that are less supportive in the development of SME’s based on the existing potential in the village Dompyong. Therefore, in the second year (2018), so there is a strategy effort in overcoming those problems.